Before Climate Change, ‘Nuclear Safety’ Was There:A Retrospective Study and Lessons-Learned of Changing Security Premises in the Arctic - Heininen, Lassi (Palgrave Pivot, 2019)
This chapter is about the environment as a special feature of Arctic geopolitics and security. The focus is on (long-range) pollution, as the first trigger of global changes in the Arctic, and ‘environmental awakening’ as a consequent reaction. This is also a retrospective study on ‘nuclear safety’ in the European Arctic, as a part of ‘environmental awakening’ and environmental politics in the North, and how it caused a shift in security premises of the Arctic states. Discourses of critical security studies - the risk society theory and ecological security - are applied to broaden our understanding of narrow traditional – national, competitive, military – security towards comprehensive one, as well as to analyze and illustrate changes in both Arctic security nexus and Arctic geopolitics.